How is the Professionalism of Online Transportation Drivers in Complying with Traffic Regulations? - Yunus, Mahmud; Soesilowati, Etty; Setyowati, Dewi Liesnoor; Arsal, Thriwaty; Rusdarti (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to determine the professionalism of drivers in complying with traffic regulations. The research method uses qualitative research with a phenomenological approach. The informants in this study were 100 drivers of online transportation and 60 consumers of online transportation in the city of Semarang. The results showed the majority of drivers had completed driving documents, the majority of drivers had used motorized vehicles according to standards, the majority of drivers had used Indonesian national standard helmets, the majority of drivers had complied with traffic signs and the majority of drivers had driven by self-safety and consumer safety. Compliance of drivers in complying with traffic regulations because it is supported by the rules set by online transportation companies. The more drivers obey traffic rules, the more professional a driver is, on the contrary if the driver often violates the rules, it shows that the driver is not yet professional in carrying out his work. This research has an impact especially on online transportation drivers in order to always maintain their professionalism in complying with traffic regulations, and for online transportation companies to always uphold the rules so that drivers can continue to be professional, especially in complying with traffic regulations.